When men were men [videorecording (DVD)] - Dick, Aidan; Dick, Aidan; Rojas, Izzi; Rojas, Izzi; Steele, Chloe; Toibin, Fiona (Indican Pictures, 2023)
In a rural Irish town, a young actor lives a double life, hiding his true self as a boy named Kieran from his religious family, where he must play the part of a girl named Kay. When he falls reluctantly in love with the boy next door, who does not know he is trans, will Kieran be able to finally face his truth?